Cause and Consequences of Youth and Adult Migration (A Case Study of Jugal Rural Municipality -1, Selang, Sindhupalchwok) - Bhattarai, Nabaraj; Thapa, Keshav (BARUN Journal, 2025)
This study attempts to analyzed the cause and consequences of youth and adult migration of Jugal Rural Municipality-1, Selang, Sindhupalchwok District. one Hundred one respondent aged 13 years and above have been selected by purposive non- probability sampling methods. Descriptive research design, quantitative research method and deductive approach are applied. Data were collected through direct interview applying the pre-structured questionnaires. Main reasons of migration of youth and adult are the better and quality education, better work opportunities, better income in destination and low infrastructure and advanced technology, weak development policy of government, family pressurize and no employment opportunities in the place of origin. Lack of human resources, low agricultural productivities, increment of remittance dependency, more cost of goods and services, brain drain, poor government policy and lack of security are the main consequences. Based on findings, there is still area for further study i.e access of better education of child due to migration, contribution of migrants for rural development, role of migrants to enhance of rural life of Nepal.